A Preliminary Screening of the Different of Secondary Metabolites Ruku-Ruku Leaves (Ocimum tenuiflorum Linnen) in West Sumatera - Hesty Parbuntari; Sri Benti Etika; Melindra Mulia; Elfanny Delvia (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Ruku-ruku leaves are used to remove distinctive odors from fish in some cuisine of West Sumatra. The characteristic odor comes from secondary metabolites especially essential oils. Therefore, secondary metabolites in ruku-ruku leaves have the potential to be further investigated as a source of bioactive compounds. The phytochemical screening of ruku-ruku leaves is a preminilary qualitative test that needs to be done to maximise its function as a medicinal plant. Based on the result data, there are some different result of flavonoid, steroids, and triterpenoids identification. Ruku-ruku leaves from Pesisir Selatan and Padang Panjang shows less flavonoid compounds tham Payakumbuh, Batusangkar, and Lubuk Alung. Both of this city and Payakumbuh also gives less steroids and triterpenoids. The factor influencing this result is caused by several factors, namely temperature, humidity, light exposure, and salinity.